Genistein enhances cytotoxic and antimigratory activities of doxorubicin on 4T1 breast cancer cells through cell cycle arrest and ROS generation - Muthi Ikawati&, Riris Istighfari Jenie&, Rohmad Yudi Utomo&, Nur Dina Amalina&, Gagas Pradani Nur Ilmawati, Masashi Kawaichi, Edy Meiyanto& (Journal of Applied Pharmaceutical Science, 2020)
Genistein (Gen) demonstrates growth induction and inhibition on several cancer cells depending on the dose. By using triple-negative breast cancer metastatic cells, 4T1, this study aimed to evaluate the cytotoxic and anti-metastatic effects of Gen in combination with doxorubicin (Dox). Gen exhibited cytotoxic effects in dose- and time-dependent manners with an IC50 value of 50 μM. Interestingly, Gen in combination with Dox enhanced the growth inhibitory effect in 48 hours and caused increases in the G2/M phase arrest, as well as apoptosis. Gen alone increased cyclin B expression that may prevent the cells to enter anaphase. Moreover, the single treatment of Gen inhibited cell migration up to 45% in 24 hours. Under gelatin zymography and immunoblotting experiments, a combination of Gen and Dox subsided the activities of matrix metalloproteinase-9 and the expression level of Rac1, thereby showing the potency of Gen as an antimigratory agent. In accordance with the growth inhibitory effect, Gen also considerably stimulated the cellular reactive oxygen species production and autophagy activity. In conclusion, Gen increased the cytotoxic activity of Dox in 4T1 cells and inhibited cell migration.
Keywords: Genistein, doxorubicin, cytotoxic, antimigration, 4T1 breast cancer cell.